La contabilidad manual y la contabilidad informatizada o computarizada, en Maynas, periodo 2023 - Santillan Rodriguez, Jorge Enrique (2025)
In the thesis that we present we mention manual accounting and computerized accounting, confirming 100% efficiency in accounting processes through computerized accounting programs, our research work, “Manual accounting and computerized accounting in Maynas, period 2023”, this research is qualitative, its study population was 30 companies, 15 businesses that believe manual accounting and 15 businesses computerized accounting or computerized accounting. In the data system in SPSS, we obtain, do you agree with computerized accounting, they think excellent 26.7% and regular 73.3%; do you agree that computerized accounting is faster than manual accounting, they think excellent 100%; do you agree that computerized accounting processes are fast, they think excellent 26. 7% and good 73.3%; You identify the reliability of computerized accounting, they think excellent 26.7% and good 73.3%; You recognize that with computerized accounting the EEFF is obtained faster, they think excellent 26.7%, good 60.00% and regular 13.3%. In the SPSS data system, we obtain, do you agree with the manual accounting, they think regular 12.5%; bad 75% and lousy 12.5%; do you agree that manual accounting remains in force, they think regular 12.5%, bad 25.00% and lousy 62.5%. That is to say, massively the businessmen no longer want to know about manual accounting.